Advancements in Coarse and Fine Particle Flotation - M. Fan; M. Mankosa; G. Luttrell (Canadian Institute of Mining, Metallurgy and Petroleum, 2010)
"Column and other non-conventional flotation approaches continue to provide benefits where conventional flotation processes have exhibited limited success. This is particularly evident with respect to flotation of ultrafine and coarse particles. Advancements in air sparging technology have provided the ability to produce finer bubbles than previously possible. The generation of finer bubbles coupled with the froth washing capabilities of a flotation column has demonstrated improvements in ultrafine particle recovery while simultaneously producing a high-grade float product. On the other side of the spectrum, the use of these sparging technologies while applying flotation fundamentals to a fluidized-bed reactor has increased the maximum floatable particle size up to and in excess of 3 mm. Benefits of higher recoveries and reduced reagent consumption have resulted from the use of these technologies. An additional benefit includes a reduction in plant grinding requirements. As such, this paper describes the application of Cavitation-Tube sparger technology and fluidized-bed flotation (HydroFloat). A review of data from industrial and pilot-scale applications is also provided.INTRODUCTIONConventional (mechanical) froth flotation is considered the workhorse of the minerals processing industry. This low-cost process makes it possible to selectively recover minerals by exploiting the difference in surface characteristics (e.g., wettability) of the valuable component and the waste material. Unfortunately, the upper particle size limit for flotation rarely exceeds 0.600 mm, and is typically maintained at less than 0.300 mm for most industrial applications. For many commercial base metal plants, the particle size range for optimum recovery is typically between 0.01 and 0.1 mm (Lynch et al., 1981). This finding is not novel. In fact, the effect of particle size on flotation recovery was studied as early as 1931 by Gaudin et al. who showed that coarse (+0.250 mm) and extremely fine particles (-0.010 mm) are more difficult to recover than particles of an intermediate size. The loss of recovery is due to inherent limitations associated with the flotation process, including bubble-particle adhesion and collision, detachment, buoyancy, and transport."